Salmonella Typhi Infections and Effect of Fluroquinolones and Third Generation Cephalosporins in Clinical Outcome - Singh, UK; Neopane, AK; Thapa, M; Aryal, N; Agrawal, K (Journal of Nepal Paediatric Society, 2011)
Background: Enteric fever is a common public health problem in Nepal. The emerging fluoroquinolone resistance to Salmonella typhi is a major concern in every hospital and is a public health problem these days. Continuous antibiotic susceptibility patterns surveillance and standard treatment policies need to be established to control MDR typhoid. Objective: To detect the increasing pattern of fluoroquinolone resistant Salmonella typhi and to correlate its clinical response to third generation cephalosporins. Materials and Method: This is a cross- sectional prospective study conducted in the pediatric ward of Birendra Hospital, Kathmandu, from September 2009 to August 2010. Forty seven children aged between 3-14 years with the diagnosis of suspected, probable and confirmed cases of Enteric fever were enrolled in the study. Data was collected and statistical analysis was done using SPSS program. Result: Culture positive enteric fever was found in 21 cases (44.68%) and positive Widal test in 18 (38.29%). Among the culture positive cases, antibiotic sensitivity was highest for Ofloxacin (95.23%), followed by third generation Cephalosporins (Ceftriaxone, Cefixime) (90.47%). A significant number of isolates were resistant to Nalidixic acid (71.42%). All cases were successfully treated with parenteral antibiotics followed by oral third generation cephalosporins without any complications and/or mortality. Conclusion: There is an increasing trend to fluoroquinolone resistant Salmonella typhi. Third generation cephalosporin can be the appropriate antibiotic for treatment.of clinically suspected cases of Enteric fever and to minimize the risk of increasing emergence of MDR enteric fever including Nalidixic acid resistant Typhoid.(NARST). Key words: Cephalosporin; drug resistance; Enteric fever; Fluoroquinolone; Salmonella typhi. DOI: http://dx.doi.org/10.3126/jnps.v31i3.5361 J Nep Paedtr Soc 2011;31(3): 216-221